2017
DOI: 10.1172/jci93396
|View full text |Cite
|
Sign up to set email alerts
|

Clinically resolved psoriatic lesions contain psoriasis-specific IL-17–producing αβ T cell clones

Abstract: Kit (QIAGEN) per the manufacturer's instructions, with overnight tissue digestion. This method generated 155-3730 ng DNA per sample.HTS analyses: immunosequencing. For each sample, DNA was extracted from skin biopsies, then TCRβ CDR3, TCRγ CDR3, TCRα CDR3, and TCRδ CDR3 regions were amplified and sequenced using immunoSEQ (Adaptive Biotechnologies). Bias-controlled V and J gene matitis, allergic contact dermatitis, and pityriasis lichenoides were obtained with IRB approval from the Pathology Specimen Locator C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
213
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(226 citation statements)
references
References 24 publications
13
213
0
Order By: Relevance
“…One reason for the differences observed between the previous studies and our own could be patient disease activity. A previous study investigating the clonality of psoriatic skin-derived CD8+ T cells showed that the TCR repertoire is polyclonal in active disease, while in resolved disease only a few dominant clones persist (28). We obtained SF effusions from joints with active inflammation, which could explain the polyclonal repertoire observed.…”
Section: Discussionmentioning
confidence: 91%
“…One reason for the differences observed between the previous studies and our own could be patient disease activity. A previous study investigating the clonality of psoriatic skin-derived CD8+ T cells showed that the TCR repertoire is polyclonal in active disease, while in resolved disease only a few dominant clones persist (28). We obtained SF effusions from joints with active inflammation, which could explain the polyclonal repertoire observed.…”
Section: Discussionmentioning
confidence: 91%
“… identified the similar motif in an independent cohort, using a different statistical approach based on the estimation of TCR recombination probability (described in detail in ). Sharing of putatively pathogenic clonotypes was also described in psoriasis . Latorre et al .…”
Section: Clonal Sharingmentioning
confidence: 82%
“…Matos et al . showed the presence of large oligoclonal subpopulations of α/β T‐cells in clinically resolved skin lesions from patients with psoriasis. A large fraction of these T‐cells was able to produce IL‐17A, which is believed to be an important driver of psoriasis pathogenesis.…”
Section: Clone Size Distribution Statisticsmentioning
confidence: 99%
“…In this report, however, V γ 9 + V δ 2 + cells were activated to produce cytokines from keratinocytes by the specific antigen, suggesting that recognition of specific antigens may be important for the development of psoriasis. Because Th17 cells94 and ILC3s95 as well as γδ 17 cells91 are also detected in the psoriatic skin, the involvement of autoimmunity and the main source of IL‐17 during the development of psoriasis still remain obscure in humans.…”
Section: γδ17 Cells In Human Inflammatory Diseasesmentioning
confidence: 99%